Plasma parameters analysis in DC and RF magnetron sputtering using finite element method - Calderón, Noely Z. (2025)
Acomprehensive comparison of results obtained by finite element modelling (FEM) and plasma diagnostics between direct current (d.c.) and radio frequency (RF) magnetron sputtering at a frequency of 13.56 MHzis presented. This research studies the influence of power in the range 20W to 90Wat a constant argon gas pressure of 1 Pa. The maximum plasma density values are observed at 90Win the d.c. mode, reaching 1.41 × 1017m−3, and 1.95 × 1016m−3 in the RF mode, with results obtained within 1μs after ignition of the plasma. The results of the experiments showed that the plasma concentration at a distance of 23mmfrom the cathode has maximum values; indicating that the electron and ion density values increase as the d.c. and RF magnetron sputtering power increases. This research aims to demonstrate the different charge density values obtained in RF and d.c. plasma withFEMto facilitate the prediction of the magnetron sputtering discharge parameters of the MatER PUCP laboratory. Given that at this moment suitable models for RF sputtering are rather scarce, the obtained plasma parameters fromFEMwill be compared to plasma parameters that were obtained Experimentally.